Effects of dietary dihydroartemisinin on growth performance, meat quality, and antioxidant capacity in broiler chickens - Xiaoxiao Pu; Yuxuan Liang; Jiafang Lian; Miaoxuan Xu; Yalan Yong; Hao Zhang; Lili Zhang; Jingfei Zhang (Poultry Science)
This study aimed to investigate the effects of dietary dihydroartemisinin on the growth performance, meat quality, and antioxidant capacity of broiler chickens. Four-hundred one-day-old Arbor Acres male broilers were randomly assigned to five treatment groups with eight replicates and ten birds each. All broilers were fed a basal diet containing 0, 5, 10, 20 or 40 mg/kg dihydroartemisinin. The results showed that dihydroartemisinin at 10 mg/kg quadratically increased ADG, and dihydroartemisinin at 10 and 20 mg/kg quadratically increased ADFI during the days 1–21 period. Compared to the control group, dihydroartemisinin at 10 and 20 mg/kg quadratically decreased the drip loss at 24 h. Dihydroartemisinin linearly and quadratically decreased the L* value of breast muscles. Dihydroartemisinin at 20–40 mg/kg linearly and quadratically decreased the MDA concentrations at D5 and D 7 of postmortem storage. Dihydroartemisinin linearly and quadratically increased the ABTS scavenging activity at D 7 of postmortem storage. Dietary 20 mg/kg dihydroartemisinin at 21 days and 40 mg/kg dihydroartemisinin at 42 days linearly and quadratically increased serum glutathione concentrations. Dihydroartemisinin at 5–40 mg/kg linearly increased serum total superoxide dismutase activity at 42 days. Dihydroartemisinin at 10–20 mg/kg quadratically decreased serum malondialdehyde contents at 42 days. At 21 days, 20 mg/kg dihydroartemisinin quadratically increased hepatic glutathione concentrations and catalase activities. Compared to the control group, 40 mg/kg dihydroartemisinin linearly and quadratically decreased hepatic malondialdehyde contents. At 42 days, 20 mg/kg dihydroartemisinin quadratically increased catalase activities and reduced the malondialdehyde contents in liver. Dihydroartemisinin quadratically increased the hepatic mRNA expression of Nrf2. Compared to the control group, dihydroartemisinin at 10 and 20 mg/kg quadratically induced the hepatic mRNA expression of HO-1. Dihydroartemisinin at 10–40 mg/kg linearly and quadratically increased the mRNA expression of CAT in liver. These results showed that dihydroartemisinin improved growth performance, meat quality, and antioxidant capacity of broiler chickens, especially at 10 and 20 mg/kg.